Development of edible coating based on Aloe vera gel to extend the shelf life of fresh-cut melon - Nabilla Putri Humala Nasution; Vita Paramita; Hermawan Dwi Ariyanto (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2023)
Edible coating has been widely used in the food and agriculture industry to maintain the quality of food, specifically fresh-cut fruits, and can extend the shelf life of fruits. In this research, Aloe vera-based edible coating was developed with the addition of carboxymethyl cellulose (CMC) and citric acid (CA) as additives to maintain the quality and extend the shelf life of fresh-cut melons (Cucumis melo L). Edible coating based on Aloe vera was made with 30% (v/v) and 50% (v/v) Aloe vera gel and mixed with 1% (w/v) and 3% (w/v) CMC as additives and 1% (w/v) citric acid. Fresh-cut melons were uncoated and coated with six combinations of Aloe vera and CMC concentrations, then stored for ten days at 30 °C. Weight loss, microbiological contamination, ascorbic acid content, titratable acidity, colorimeter analysis, and sensory analysis were evaluated every two days to assess the quality of fresh-cut melons. The findings indicated that the samples coated with 50% (v/v) Aloe vera gel and 3% (w/v) CMC had superior effectiveness and the highest quality in terms of weight loss, microbiological contamination, ascorbic acid content, titratable acidity, colorimeter analysis, and sensory evaluation.